Building a more competent security sector: The case of UNMIL and the Liberian National Police. Issue 1 (1st January 2016) - Karim, Sabrina; Gorman, Ryan
ABSTRACT: Increasingly UN peacekeeping missions are helping to implement security sector reforms (SSR), including gender reforms, targeted at the local police of host countries. This study uses the UN Mission in Liberia (UNMIL) and the Liberian National Police (LNP) as a way to explore whether SSR may have helped improve individual officers' professional and gender competencies. Conducting a novel lab-in-the-field experiment, we test the individual competencies of 612 LNP officers, also analysing possible determinants of these competencies. We find that most officers have knowledge about statutory crimes and evidence gathering, most officers participate in group activities, almost half are aware of gendered crimes and that male and female officers are equally competent. However, our results suggest that the reforms are at the nascent stages of working, and that more focus should be put into basic training and gender mainstreaming in the Liberian National Police, especially as new recruits are added.